Hereditary hemorrhagic telangiectasia in a pregnant woman - Mabel González Escudero; Marilyn Sosa Estébanez; Noel David Pérez Acosta (Centro Provincial de Información de Ciencias Médicas, 2018)
The case report of a 16 years pregnant woman is presented who went to the dermatology and genetics services due to cutaneous lesions. After carrying out the pertinent studies, the diagnosis of hereditary hemorrhagic telangiectasia was considered. She was referred to "Mártires del 9 de Abril" Hospital in Sagua La Grande with vaginal, rectal and labium bleeding that was controlled. Some consultations with other specialists were carried out to guarantee the multidisciplinary care during pregnancy and childbirth. The patient had a favorable clinical course until having her baby through an eutocic childbirth.